Writing Unleashed Content and Structure - Priebe, Sybil; Marman, Ronda; Anderson, Dana (Open textbook library., 2020)
Welcome to Writing Unleashed, designed for use as a textbook in first-year college composition programs, written as an extremely brief guide for students, jam-packed with teachers’ voices, students’ voices, and engineered for fun.